2021
DOI: 10.2176/nmc.oa.2021-0017
|View full text |Cite
|
Sign up to set email alerts
|

Small Unruptured Aneurysm Verification-prevention Effect against Growth of Cerebral Aneurysm Study Using Statin

Abstract: Several basic experimental studies have demonstrated that statins have beneficial effects for intracranial aneurysm (IA). Clinical studies on unruptured IAs, however, remain limited to four retrospective studies that have reached different conclusions. This study was the first open-label, multicenter, randomized controlled trial to assess the preventive effects of atorvastatin. Patients with unruptured small saccular IAs were randomly assigned to statin and control groups. The primary endpoint was a composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…There is one completed RCT comparing treatment with a statin versus no statin on the risk of growth and rupture of an intracranial aneurysm, but this trial had no data on death or dependency as outcome measure. 65 In this open-label, multicentre, randomised controlled trial the effect of atorvastatin on the risk of aneurysm growth was studied. The primary endpoint was a composite of aneurysm growth of ⩾0.5 mm, new bleb formation confirmed from magnetic resonance (MR) angiography, and rupture.…”
Section: Resultsmentioning
confidence: 99%
“…There is one completed RCT comparing treatment with a statin versus no statin on the risk of growth and rupture of an intracranial aneurysm, but this trial had no data on death or dependency as outcome measure. 65 In this open-label, multicentre, randomised controlled trial the effect of atorvastatin on the risk of aneurysm growth was studied. The primary endpoint was a composite of aneurysm growth of ⩾0.5 mm, new bleb formation confirmed from magnetic resonance (MR) angiography, and rupture.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon further reduces the elasticity of the cerebral vascular wall, making it less able to adapt to altered hemodynamics, promotes IA progression, and increases the risk of rupture ( 59 61 ). NF-κB elevates the transcription of various pro-inflammatory genes such as COX-2, CCL-2, MMP , and iNOS , and the inflammatory response is involved in the progression and rupture of IA ( 62 , 63 ). Moreover, macrophage infiltration and NF-κB activation are reduced if macrophages are specifically absent or in the mutants of the NF-κB inhibitory protein.…”
Section: Discussionmentioning
confidence: 99%
“…There was no statistically significant difference between the two treatment groups, but the study was ended prematurely due to slow enrollment. 51…”
Section: Medical Treatmentsmentioning
confidence: 99%
“…There was no statistically significant difference between the two treatment groups, but the study was ended prematurely due to slow enrollment. 51 Management of hypertension is recommended for reduction of aneurysm rupture risk. While there is no prospective randomized controlled trial data yet available, one prospective study included 272 patients with unruptured intracranial aneurysms, and found that patients with uncontrolled hypertension, in comparison to nonhypertensive patients, had a high hazard ratio for aneurysm growth (6.1, 95% confidence interval [CI]: 2.4-15.4), compared with controlled hypertensive patients (1.6, 95% CI: 0.6-3.8).…”
Section: Medical Treatmentsmentioning
confidence: 99%